Toxicokinetics and tissue dynamics approaches to evaluate the accumulation and elimination of cadmium in black soldier fly larvae - Jie Zhang; Xuelian Xu; Chunyan Tang; Zhihui Shi; Yujia Wan; Huan Qiu; Rui Feng; Fengfeng Li; Fen Zhu (Ecotoxicology and Environmental Safety)
The black soldier fly larvae (BSFL) is a highly valued resource insect, renowned for its efficient and eco-friendly approach to the treatment of organic waste. A crucial matter that demands clarification is whether the heavy metals are eliminated or remain within BSFL bodies. Our research focused on the toxicokinetic and the dynamic tissue changes of cadmium (Cd) in BSFL exposed to low (50 mg/kg), moderate (300 mg/kg), and high levels (700 mg/kg) of Cd stress, with the goal of offering a novel perspective on this matter. Our results demonstrated a negative correlation with the BAFkinetic and a positive correlation with the BAF as Cd concentrations increased. BSFL exhibited significant rates of Cd uptake, with values for Cd50, Cd300, and Cd700 being K1= 1.3998, 0.9794, and 0.9023 g substrate glarvae−1 day−1, respectively. Across all treatments, BSFL were capable of excreting Cd, with a DT50 less than 2 days. The gut, particularly the midgut, was identified as the primary tissue for Cd enrichment. The anterior midgut played a pivotal role as a critical organ during high Cd exposure, while the middle midgut served as a stable storage organ. The posterior midgut was the preferred tissue for Cd accumulation. Following bioconversion by BSFL, the concentration and bioavailability of Cd in the resulting residue were altered. In conclusion, BSFL possess significant potential for swiftly mitigating high-concentration Cd pollution. Moreover, the application of a 2-day short-term elimination feeding strategy can significantly elevate the food safety and safety for animal consumption of BSFL.